A Biomimetic Synthesis of (±)‐Basiliolide B1. Issue 42 (27th August 2014) - Min, Long; Zhang, Yang; Liang, Xuefeng; Huang, Junrong; Bao, Wenli; Lee, Chi‐Sing
Abstract A highly diastereoselective and practical biomimetic total synthesis of (±)‐basiliolide B has been achieved through the study of the two proposed biosynthetic pathways (O‐methylation and O‐acylation) for the unprecedented 7‐methoxy‐4, 5‐dihydro‐3H‐oxepin‐2‐one (C ring). The synthesis featured a cyclopropanation/ring opening strategy for establishing the stereogenic centers at C8 and C9, a biomimetic 2‐pyrone Diels–Alder cycloaddition for the synthesis of the ABD ring system, and finally a highly efficient biomimetic intramolecular O‐acylation for the C ring formation. This result provides an important perspective on the biosynthetic origin of the unprecedented 7‐membered acyl ketene acetal moiety of the C ring.